Student and Staff Perceptions of the International Postgraduate Student Experience: A Qualitative Study of a UK University - Bird, Emma L. (Journal of International Students, 2017)
This study aimed to explore student and staff perceptions of academic, personal and social factors influencing the international postgraduate student experience at a UK University. Focus groups were conducted with international students enrolled in a Master in Public Health programme (n=10). An in-depth survey containing open-ended questions was completed by university staff that contribute to postgraduate teaching (n=12). Qualitative data were analysed using Thematic Analysis. Student and staff perceptions of the international postgraduate student experience were broadly similar, although some discrepancies were identified. Five themes emerged: adjustment to academic expectations; adjustment to academic conventions; programme internationalisation; adjustment to the local culture; and, future plans. Findings add to the limited evidence base on the international postgraduate student experience in UK universities